Albania’s Plan: Response to COVID-19 - Degjoni, Rudina; Loxha, Ilirjana (European Journal of Economics and Business Studies, 2020)
The current novel coronavirus (COVID-19) outbreak, which began in December 2019, represents a significant challenge for Albania, as well as for the entire world. This study considers that Albania has prepared several action plans over the years related to pandemic influenza preparedness, health security, and health emergencies. The result shows that sharing information about the preparedness of Albania’s plan has a significant positive impact on the response adequately and in a timely manner, offering protection to the population. This paper first investigates the novel nature of the virus during a pandemic situation in Albania and proposes public protection plans to respond to the coronavirus. In brief, the current main objectives in Albania are to create a protected environment, update information and create response measures for the Albanian population. The results show that the measures taken are helping the health indicators to stay constant and decrease the curve of the pandemic.Keyword: coronavirus, measures, indicators, response, Albanian population
Keywords: word: coronavirus, measures, indicators, response, Albanian population